PENGARUH PEMBERIAN DOSIS PUPUK KALIUM DAN MACAM PUPUK KANDANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN UBI JALAR (Ipomoea batatas L.) - irfan rifani; Abdul Basit; Mahayu Woro Lestari (AGRONISMA, 2020)
This study aims to determine the effect of potassium doses and types of manure on the growth and yield of sweet potato (Ipomea batatas L). In this study using a factorial randomized block design. Factor 1 is a dose of potassium (K) consisting of three levels, namely: K1 = 50 kg.ha- KCl, K2 = 100 kg.ha- KCl, and K3 = 150 kg.ha- KCl. Factor 2 is a type of manure (N) consisting of three levels, namely: N0 = without manure, N1 = cow manure, and N2 = chicken manure. Each treatment was repeated 3 times with samples of each 3 sweet potato plants. The results of this study indicate that the administration of KCl dosage and types of manure do not provide a significant interaction effect on growth, namely plant length, number of leaves, and leaf area as well as yield of sweet potato and KCl dose giving the best growth and yield of sweet potato production at the dose KCl of K3 treatment that is 150 kg.ha- as much as 2744.44 g and the provision of various kinds of manure gave the best growth and yield of sweet potato in N2 fertilizer namely chicken manure as much as 2733.33g.